2016
DOI: 10.1093/molbev/msw219
|View full text |Cite
|
Sign up to set email alerts
|

Insights from the Shell Proteome: Biomineralization to Adaptation

Abstract: Bivalves have evolved a range of complex shell forming mechanisms that are reflected by their incredible diversity in shell mineralogy and microstructures. A suite of proteins exported to the shell matrix space plays a significant role in controlling these features, in addition to underpinning some of the physical properties of the shell itself. Although, there is a general consensus that a minimum basic protein tool kit is required for shell construction, to date, this remains undefined. In this study, the sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
144
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 117 publications
(157 citation statements)
references
References 105 publications
5
144
0
Order By: Relevance
“…The mineralogy and shell microstructure of these species may account for that differences. The C. gigas shell is purely calcite: the outer shell layers are calcite prisms, the middle shell layers are chalky calcite and the inner shell layer are foliated calcite18. In contrast, M. truncata shell is composed only of aragonite.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The mineralogy and shell microstructure of these species may account for that differences. The C. gigas shell is purely calcite: the outer shell layers are calcite prisms, the middle shell layers are chalky calcite and the inner shell layer are foliated calcite18. In contrast, M. truncata shell is composed only of aragonite.…”
Section: Resultsmentioning
confidence: 99%
“…Collectively, comparison of the shell proteomes for sequence similarity gives some clues about the relationships between evolution and sequence conservation. However, it has been suggested that the similarity in SMPs depends not only on the evolutionary distance but is also influenced by mineralogy of shell, parallel evolution, adaptation to the environment etc18.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations